Assessing structure-function impacts on Vitellogenin by leveraging allelic variant found in honey bee subspecies Apis mellifera mellifera - Vilde Leipart; Oriol Gracia Carmona; Christine Orengo; Franca Fraternali; Gro V. Amdam (iScience)
Summary: Advances involving artificial intelligence (AI) and experimental structure determination can provide detailed pictures of complex protein structures and their variations. Vitellogenin (Vg), derived from the honeybee (Apis mellifera), is an essential protein for reproduction in most egg-laying animals and can regulate behavior and provide immunological support in some species. Despite its importance, information on Vg’s structure-function relationships is limited. Leveraging a unique dataset of 1,086 fully sequenced Vg alleles, we identify a population-specific 9-nucleotide deletion in a central Vg domain of the locally endangered A. m. mellifera subspecies. Due to the population’s history of near extinction and human intervention, an assessment of this Vg variant is theoretically interesting and relevant for subspecies conservation efforts. Structural bioinformatics, molecular dynamics simulations, and a transformer-based indel predictor (IndeLLM) demonstrate that the deletion does not disrupt Vg’s structure and stability. Generalizable results may extend to other egg-laying animals of ecological and economic importance.